Cancer incidence in North Cyprus (1990-2004) relative to European rates - Hinçal, Evren; Taneri, Bahar; Taneri, Ufuk; Djamgoz, Mustafa B.A. (Asian Pacific Organization for Cancer Prevention, 2008)
Cancer incidence in North Cyprus (NC), deemed an interesting epidemiological case due to possible contrasting prevailing factors in relation to South and North Europe (SE and NE), was evaluated for the period 1990-2004. Age standardized rates (ASRs) and average age of incidence (AAI) values were determined for 12 different cancers, separately for males and females. Annual trends were analyzed using linear regression slopes. Absolute values were compared by two-tailed t-tests. The order of prevalence for incidences of male (M) cancers were: lung, skin, colorectal, prostate, brain, bladder, liver and stomach. Similarly, for females (F) they were: breast, gynaecological, skin, colorectal, lung, liver, brain, stomach and bladder. The following cancer cases were more common than in SE and NE: lung (M) and skin (both genders). Breast (F), prostate, stomach (F), bladder (both sexes), cervix and corpus were less frequent; the rest were comparable. There was no difference in the annual trends of ASR or AAI for NC, compared with SE or NE. Thus cancer incidence in NC shares many quantitative features with the rest of Europe. The worst cases could be improved by reducing smoking and protection from the sun.
Keywords: Cancer incidence; Cyprus; Diet; Environment; Europe; Mediterranean